Pekerja Indonesia di Belanda: Studi Kasus Pekerja Tidak Terampil dan Tidak Terdokumentasi - Amin Mudzakkir (Jurnal Kajian Wilayah, 2012)
This paper shows how the terms of unskilled and undocumented are constructed in the dynamics of migration and citizenship in the Netherlands. In particular, this paper look at the dynamics in the case study of Indonesian workers. Conceptual relationship between the terms of unskilled and undocumented until a certain level is causal. Beginning with a discussion about the past relations between Indonesia and the Netherlands, this paper describes some of the story of Indonesian workers in the Netherlands, including the activities of labor organizations struggling for immigrant workers rights guaranteed by the law and facilitated by democratic political environment.Keywords: unskilled, undocumented, migration, citizenship, Indonesia Workers, the Netherlands.